Effect of drying technique on some physical properties of cross-linked high amylose/pectin mixtures - Soares, Grazielle A. [UNESP]; Carbinatto, Fernanda M. [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Evangelista, Raul Cesar [UNESP] (Taylor & Francis, 2013)
Polymers mixtures as well as cross-linking reactions are approaches that have been used successfully to modulate the polymers characteristics in order to improve the control over drug release rate. High amylose and pectin are polysaccharides frequently used to prepare drug delivery systems. Since the drying technique can strongly influence the properties of such systems, the aim of this work was to characterize high amylose/pectin mixtures cross-linked with sodium trimetaphosphate and dried by different techniques-oven and lyophilization. The results showed that samples dried by lyophilization presented reduced particle size, higher porosity and higher swelling ability than the samples dried in oven. Besides, lower thermal stability and different diffraction patterns showed by the former particles should reflect the structural changes as a function of drying technique. © 2013 Informa Healthcare USA, Inc.
Keywords: Lyophilization; Oven drying; Swelling ability; Thermal behavior; X-ray diffraction; amylose; pectin; freeze drying; high temperature procedures; oven drying; particle size; porosity; thermostability; X ray diffraction; Amylose; Cross-Linking Reagents; Drug Compounding; Particle Size; Pectins; Polymers; Polyphosphates